Black butler III - Toboso, Yana, 1984- (Toboso, Yana, 1984- Black butler, 2010)
Ciel is in danger of sinking into darkness after being attacked by Madame Red, who is subsequently killed by Grelle before she is taken away by the shinigami William Spears. Then, a party organized to cheer Ciel nearly runs into trouble when a hunting group is attacked by a bear which Sebastian dispatches.